De novo WNT5A‐associated autosomal dominant Robinow syndrome suggests specificity of genotype and phenotype. (24th May 2014) - Roifman, M.; Marcelis, C.L.M.; Paton, T.; Marshall, C.; Silver, R.; Lohr, J.L.; Yntema, H.G.; Venselaar, H.; Kayserili, H.; van Bon, B.; Seaward, G.; FORGE Canada Consortium; et al.
<x xml:space="preserve">Abstract</x> Robinow Syndrome (RS), a rare skeletal dysplasia syndrome, is characterized by dysmorphic features resembling a fetal face, mesomelic limb shortening, hypoplastic external genitalia in males, and renal and vertebral anomalies. Both autosomal dominant and autosomal recessive patterns of inheritance have been reported. Since the description of autosomal dominant Robinow Syndrome (ADRS; OMIM 180700) in 1969 by Meinhard Robinow and colleagues, the molecular etiology remained elusive until only recently. WNT5A was proposed to be the candidate gene for ADRS, as mutations were found in two affected families, one of those being the originally described index family. We report three families with RS caused by novel heterozygous WNT5A mutations, which were confirmed in the first family by whole exome sequencing, and in all by Sanger sequencing. To our knowledge, this is the largest number of published families with ADRS in whom a WNT5A mutation was identified. Families 1 and 2 are the first cases showing de novo inheritance in the affected family members and thus strengthen the evidence for WNT5A as the causative gene in ADRS. Finally, we propose WNT5A mutation specificity in ADRS, which may affect interactions with other proteins in the Wnt pathway.